HUBUNGAN PENGETAHUAN KEBERSIHAN GIGI DENGAN GINGIVITIS PADA WANITA PUBERTAS DI MTsS BABAH KRUENG - Suryani, Linda (Jurnal Ilmiah Keperawatan, 2021)
Gingivitis undergoes gum discoloration from reddish to bluish red, in accordance with the increase in the process of ongoing inflammation. Based on the initial examination of 13 students there were 6 students with mild gingivitis, 7 students having moderate gingivitis. The purpose of this study was to determine the relationship of knowledge about oral and dental hygiene against gingivitis in puberty women aged 12-15 years at MTs SBabah Krueng Pidie Jaya in 2019. Gingivitis undergoes gum discoloration from reddish to bluish red, in accordance with the increase in the process of ongoing inflammation. Based on the initial examination of 13 students there were 6 students with mild gingivitis, 7 students having moderate gingivitis. The purpose of this study was to determine the relationship of knowledge about oral and dental hygiene against gingivitis in puberty women aged 12-15 years at MTs SBabah Krueng Pidie Jaya in 2019